EVALUATION OF CLINICAL EFFICACY OF PARADADI MALHARAM IN DUSTA VRANA - Vali Jyothirmai P; Badari Narayana V; Reddy Bhaskara K.V.V.; Rama Mohana Rao G.; Sri Durga Ch. (International Journal of Applied Ayurved Research, 2016)
As per Ayurveda concern, healing of vrana is a natural process of the body supported by doshas and dhatus, but it should be protected from Dosha Dusti, Dhatudusti and sankramana of different forms( Rakshas;micro-organisms) can afflict the Vrana and delay the Vrana Ropana. In Ayurveda, chronic ulcer is dealt under Dusta vranas, chronic ulcer has got all characteristic features of Dustavrana, a frequently encountered problem. Chronic ulcers are shown to be the most common cause for hospitalization and prolonged stay for proper wound care. Still wound management continues to be a subject of speculation in chronic ulcers. An effective external application (An ulcer which is not cured by treating with hundreds of drugs is cured definitely by this efficacious drug as per the sloka reference) Paradadi Malharam was prepared with rasoushadhies as rasa drugs can combat the diseases with high absorption rate and quick action. The pharmaceutical procedures adopted in this study are Shodhana, Mardana, Nimajjana and Malhara nirmana. An attempt has been made to study its efficacy clinically on Dustavrana through “Non- Randomised open labelled clinical trial over a sam-ple of 30 patients with restricted/purposive sampling. Paradadi Malharam gives statistically highly significant relief in all the symptoms (p<0.0001). This therapy had shown moderate improvement in 53.33% of patients and Marked improvement in 46.66% patients.